Predicting difficult airway in morbidly obese patients using ultrasound - Akin, Sevim; Yildirim, Mustafa; Arta, Hakan; Bolat, Esef (Tubitak Scientific & Technological Research Council Turkey, 2024)
Background/aim: Difficult mask ventilation and difficult intubation are more common in obese patients. Ultrasound is a reliable and noninvasive method for evaluating the airway. The aim of this study was to investigate the contribution and availability of anterior neck soft tissue (ANS) thickness at different levels, tongue volume (TV), hyomental distance (HMD), the ratio of preepiglottic distance to distance between the epiglottis and the midpoint of vocal cords (PE/E-VC) measured by ultrasonography in predicting difficult airway in morbidly obese patients. Materials and methods: Between March 2020 and November 2020, patients aged >= 18 years with a body mass index (BMI) of >= 40 kg/m2 who underwent elective surgery under general anesthesia were included in this prospective study at Firat University Hospital. During the preoperative evaluation of patients, ultrasound was used to measure and record TV, ANS thickness at different levels, HMD, and ratio of PE/E-VC. Patients with difficult intubation were identified using the Cormack-Lehane classification system. Patients whohad difficulties with balloon mask ventilation were recorded. Subsequently, the parameters of patients with easy and difficult intubation were compared. In addition, the parameters of patients with easy and difficult mask ventilation were also compared.Results: The preepiglottic ANS thickness at the level of the thyrohyoid membrane and the PE/E-VC value in obese patients with difficult intubation were significantly greater than in obese patients with easy intubation (p < 0.001). In addition, TV (p < 0.001), preepiglottic ANS thickness at the thyrohyoid membrane level (p < 0.001), ANS thickness at the thyroid isthmus level (p = 0.002), ANS-suprasternal notch thickness (p = 0.004), and PE/E-VC (p = 0.005) values were significantly greater in obese patients with difficult mask ventilation. Conclusion: Ultrasound may be a useful tool for predicting difficult airway and difficult mask ventilation. For this purpose, ANS thickness at different levels, PE/E-VC, and TV values measured by ultrasound can be used.
Keywords: Obesity; difficult airway; ultrasound; intubation; neck